Effects of different exercise types on vascular endothelial function in individuals with abnormal glycaemic control: a systematic review and network meta-analysis - Zongxiang Li; Shengyao Luo; Xuebing Bai; Lu Huang; Hongyan Guo; Song Chen; Dan Wang (PeerJ)
Background Brachial artery flow-mediated dilation (FMD) is a key marker of endothelial function, often impaired in individuals with abnormal glycemic control. While exercise has been shown to improve brachial artery FMD, the relative efficacy of different exercise modalities remains unclear. This study employed a network meta-analysis (NMA) to compare the effects of various types of exercise on FMD. Methods A comprehensive search of PubMed, Embase, Cochrane, Web of Science, and EBSCO databases identified randomized controlled trials evaluating the effects of exercise on brachial artery FMD up to January 2025. Two independent reviewers screened studies, extracted data, and assessed risk of bias. Eligible studies were assessed for bias using version 2 of the Cochrane Risk of Bias tool. Stata 16.0 was used for the NMA. Results Seventeen studies with 797 participants (prediabetes: 76; T2DM: 721) were included. Aerobic interval exercise (AIE) significantly improved FMD (MD = 2.23%, 95% CI [1.0 9%–3.37%], P < 0.05), followed by mind-body exercise (MBE) (MD = 1.97%, 95% CI [0.60%–3.33%], P < 0.05). Combined exercise (CE) (MD = 1.17%, 95% CI [0.13%–2.21%], P < 0.05) and aerobic continuous exercise (ACE) (MD = 1.20%, 95% CI [0.52%–1.87%], P < 0.05) also showed significant improvements. SUCRA values indicated that AIE (89.0) and MBE (80.1) were the most effective in improving FMD, followed by CE (51.0), ACE (50.9), and resistance exercise (RE) (20.1), all outperforming the control group (SUCRA = 9.2). Conclusion AIE was the most effective modality for improving FMD, with MBE serving as a viable alternative for individuals with lower fitness or cardiovascular concerns. CE and ACE also provided benefits, while RE was less effective. Future studies should focus on long-term outcomes and personalized exercise strategies.